When we were real : a novel - Gregory, Daryl (Saga Press, 2025)
"From multiple award-winning author Daryl Gregory comes a madcap adventure following two friends on a cross-country bus tour through the mind-boggling glitches in their simulated world as they grapple with love, family, secrets, and the very nature of reality in a simulation"--